2012
DOI: 10.1149/2.024210jes
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Simulation of Galvanostatic Discharge of LiCoO2Cathode Based on X-ray Nano-CT Images

Abstract: Based on the experimentally determined microstructure of a lithium ion battery (LIB) cathode electrode using X-ray nano-CT technology, a three dimensional simulation framework of galvanostatic discharge with finite volume method is presented. The tomography data were used to evaluate the homogeneity of porosity and tortuosity of the electrode. With this approach, galvanostatic discharge processes at different C rates were simulated and the local effects in the LIB cathode electrode during discharge processes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
113
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 45 publications
1
113
0
1
Order By: Relevance
“…This is because they can lead to loss of capacity, local over-charge or over-discharge, or unsafe conditions (e.g., loss of oxygen in the case of transition metal oxides at high SOC). [19][20][21] Thus, understanding the formation mechanism of the non-uniformity is fundamentally interesting and practically important. To study heterogeneity at the particle level, it is useful to prepare samples by chemical delithiation using an oxidant such as NO2BF4 or Br2.…”
Section: Introductionmentioning
confidence: 99%
“…This is because they can lead to loss of capacity, local over-charge or over-discharge, or unsafe conditions (e.g., loss of oxygen in the case of transition metal oxides at high SOC). [19][20][21] Thus, understanding the formation mechanism of the non-uniformity is fundamentally interesting and practically important. To study heterogeneity at the particle level, it is useful to prepare samples by chemical delithiation using an oxidant such as NO2BF4 or Br2.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Weidemann et al [20] developed a computational model that resolves the complex 3D microstructure of LIB cathodes and showed the local variations of lithium ion concentration and electrostatic potential in realistic electrodes. In our previous studies, the 3D numerical simulation also revealed the non-uniform spatial distributions of the potential, concentration, intercalation reaction rate, heat generation rate, and stress development [21][22][23]. The realistic microstructure of LIB electrodes play a key role to study morphological effects on lithium ion transport, electrochemical kinetics, material degradation, and cell performance.…”
Section: Introductionmentioning
confidence: 93%
“…Although the porous-electrode theory and simple active material structure models can be used to investigate LIB thermal effects with less time consumption of numerical simulation, the results cannot account for non-uniform local heat generation and temperature distribution in LIBs. Because of the real complicated morphology of LIB electrodes [34][35][36][37][38], the interaction between electrode particles can cause non-uniform spatial distribution of the physical and electrochemical fields [39][40][41] and heat generation. Therefore, a numerical approach with the details of electrode microstructure is necessary for the study of intricate local thermal effects in LIB electrodes.…”
Section: Introductionmentioning
confidence: 99%